Examination of CEO–CFO Social Interaction through Language Style Matching: Outcomes for the CFO and the Organization - Shi, Wei; Zhang, Yan; Hoskisson, Robert E. (Academy of Management Journal, 2019)
This study proposes that CEO–CFO “language style matching”—a form of unconscious verbal mimicry based on function words—can provide insights into social interaction processes between CEOs and CFOs. We argue and empirically verify that high CEO–CFO language style matching reflects CFOs’ strong attempts to ingratiate themselves with CEOs. Because ingratiation with superiors can lead to the superiors’ positive evaluations of subordinates, CFOs who exhibit higher language style matching with CEOs will receive higher compensation and are more likely to become board members of the associated firms. In addition, the proposed relationships will be stronger when CEOs are more powerful. Yet, in the presence of high CEO–CFO language style matching, CFOs are less likely to voice different viewpoints and challenge CEOs in strategic decision processes. As a result, firms tend to undertake more mergers and acquisitions, and such mergers and acquisitions will be paid with a low percentage of cash (vs. stock) and realize lower announcement returns. Using a sample of over 2,000 U.S. firms from the period 2002–2013, we find empirical support for these predictions.